2016
DOI: 10.1111/jonm.12385
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers’ decision-making in daily unit operation in peri-operative settings: a cross-sectional descriptive study

Abstract: The results can be used when planning decision support systems and when defining the nurse managers' tasks in peri-operative settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 19 publications
(42 reference statements)
0
46
0
Order By: Relevance
“…This study showed that decision‐making skills were relevant for nurse managers (Karathanasi et al, ; Schroeder & Worral‐Carter, ; Siirala et al, ). An earlier study carried out in the field of acute health care indicated that decision‐making differed between professionals and nurse managers’ decision‐making was far‐reaching (Lundgrén‐Laine et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This study showed that decision‐making skills were relevant for nurse managers (Karathanasi et al, ; Schroeder & Worral‐Carter, ; Siirala et al, ). An earlier study carried out in the field of acute health care indicated that decision‐making differed between professionals and nurse managers’ decision‐making was far‐reaching (Lundgrén‐Laine et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Analysis revealed that nurse managers often had a bachelor's degree (Karathanasi et al, ; Martin & Waring, ; Rudolfsson & Flensner, ; Rudolfsson et al, ) and few were academically qualified (Kondrat, ; Rudolfsson & Flensner, ; Rudolfsson et al, ). In one study (Siirala et al, ), there was no mention of educational degrees for nurse managers.…”
Section: Key Issuementioning
confidence: 99%
See 3 more Smart Citations